Prototipe Sistem Kontrol Pemadam Kebakaran Pada Rumah Berbasis Arduino Uno dan ESP8266 (Komputika : Jurnal Sistem Komputer, 2021)
The fire was one of the incidents that disturbed the comfort of the homeowner. When a fire occurs there is no early warning to the homeowner concerned. In its handling also often we find the fire department itself difficult to extinguish the fire. The research method used is experimental research by conducting trials on tools to extinguish house fires with output given in the form of flames and smoke using fire sensor modules and MQ7 sensors. Test results on the fire sensor obtained a maximum distance of detecting the flame of 120 cm. The MQ7 sensor detects smoke when smoke levels exceed 100 PPM. The DHT22 sensor can read room temperature with an accuracy value of 97.1%. System success rate when working on living room is 100%, room 1 is 100%, room 2 is 100% and bathroom is 100%. The average percentage rate of overall success of the system in work is 100%.Keywords - Arduno uno, house fire, Esp8266, flame detector, MQ7, DHT22.